2011
DOI: 10.1111/j.1475-4754.2010.00581.x
|View full text |Cite
|
Sign up to set email alerts
|

Employing Tl Methods for the Verification of Macroscopically Determined Heat Alteration of Flint Artefacts From Palaeolithic Contexts

Abstract: The reconstruction of past human use of fire is often based on the presence of fire in archaeological sites as evidenced by alterations of lithic material. Here, a simple test based on thermoluminescence (TL) methods is used as a verification tool for the macroscopic identification of burning damage on flint microartefacts from the Early and early Middle Pleistocene site of Gesher Benot Ya'aqov (Israel). The small dimensions of the microartefacts often prevented the removal of the outer surface, for which the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 29 publications
(56 reference statements)
1
16
1
Order By: Relevance
“…Some of the most intensive research on early use of fire has focused on the site of Gesher Benot Ya'akov in the Jordan Valley (Israel), dated to between 0.7 and 0.8 Ma, where pot-lid fractures, characteristic rounded concave scars produced by heat-induced removal of planoconvex flakes, have been used to identify burned microdebitage (14). Thermoluminescence analysis supports the identification of burned microdebitage, and its spatial distribution, together with the presence of charred wood, seeds, and grains led to the identification of "phantom hearths" (5,15,16). Nevertheless, the evidence and acceptance for controlled use of fire at any of the Acheulean sites noted earlier remains controversial.…”
Section: Previous Research On Early Evidence Of Firementioning
confidence: 99%
“…Some of the most intensive research on early use of fire has focused on the site of Gesher Benot Ya'akov in the Jordan Valley (Israel), dated to between 0.7 and 0.8 Ma, where pot-lid fractures, characteristic rounded concave scars produced by heat-induced removal of planoconvex flakes, have been used to identify burned microdebitage (14). Thermoluminescence analysis supports the identification of burned microdebitage, and its spatial distribution, together with the presence of charred wood, seeds, and grains led to the identification of "phantom hearths" (5,15,16). Nevertheless, the evidence and acceptance for controlled use of fire at any of the Acheulean sites noted earlier remains controversial.…”
Section: Previous Research On Early Evidence Of Firementioning
confidence: 99%
“…Macroscopically observable alterations on lithic artifacts, as documented for the Neumark-Nord 2 assemblage, are indicative of heating temperatures of at least 300-350°C (Sergant et al 2006;Richter 2007;Richter et al 2011), which is confirmed for the pieces submitted to a TL heating plateau test (Richter and Krbetschek 2014). Thermal fracture, as observed on many of the studied pieces, has been shown to take place when the material is exposed to temperatures in excess of 400°C (Purdy and Brooks 1971;Domanski et al 1994;Domanski and Webb 1992;Buenger 2003).…”
Section: Thermally Altered Flint Artifacts and Faunal Remainsmentioning
confidence: 71%
“…Fire characterises the ‘Acheulean’ Gesher Benot Ya'akov site at the onset of the Brunhes chron, c. 078 Ma (Goren-Inbar et al 2004; Alperson-Afil & Goren-Inbar 2010; Richter et al . 2011; Alperson-Afil 2012). Barely 140km south-west of CNERQ, magnetostratigraphy identified the “Matuyama-Brunhes boundary only a few metres below the fossil/tool-bearing levels” (Scott & Gibert 2009: 82) at the open Solana del Zamborino site, where excavation uncovered five stones surrounding a possible hearth area containing carbonised wood (“madera carbonizada”, Botella López et al .…”
Section: Early Fire and Mid-quaternary Human Evolutionmentioning
confidence: 99%
“…2012, who do not exempt Gesher Benot Ya'akov in that regard, contra Richter et al . 2011; Alperson-Afil 2012). At Swartkrans Cave, evidence of combustion (Skinner et al .…”
Section: Early Fire and Mid-quaternary Human Evolutionmentioning
confidence: 99%